Evidence of a role of tumor necrosis factor alpha in refractory asthma. - Berry, M; Hargadon, B; Shelley, M; Parker, D; Shaw, D; Green, R; Bradding, P; Brightling, C; Wardlaw, A; Pavord, I (2006)
BACKGROUND: The development of tumor necrosis factor alpha (TNF-alpha) antagonists has made it feasible to investigate the role of this cytokine in refractory asthma. METHODS: We measured markers of TNF-alpha activity on peripheral-blood monocytes in 10 patients with refractory asthma, 10 patients with mild-to-moderate asthma, and 10 control subjects. We also investigated the effects of treatment with the soluble TNF-alpha receptor etanercept (25 mg twice weekly) in the patients with refractory asthma in a placebo-controlled, double-blind, crossover pilot study. RESULTS: As compared with patients with mild-to-moderate asthma and controls, patients with refractory asthma had increased expression of membrane-bound TNF-alpha, TNF-alpha receptor 1, and TNF-alpha-converting enzyme by peripheral-blood monocytes. In the clinical trial, as compared with placebo, 10 weeks of treatment with etanercept was associated with a significant increase in the concentration of methacholine required to provoke a 20 percent decrease in the forced expiratory volume in one second (FEV1) (mean difference in doubling concentration changes between etanercept and placebo, 3.5; 95 percent confidence interval, 0.07 to 7.0; P=0.05), an improvement in the asthma-related quality-of-life score (by 0.85 point; 95 percent confidence interval, 0.16 to 1.54 on a 7-point scale; P=0.02), and a 0.32-liter increase in post-bronchodilator FEV1 (95 percent confidence interval, 0.08 to 0.55; P=0.01). CONCLUSIONS: Patients with refractory asthma have evidence of up-regulation of the TNF-alpha axis. (ClinicalTrials.gov number, NCT00276029.).